The US dollar- scenario of a world currency - Hans E. Büschgen (Intereconomics, 1987)
The exchange rate of the US dollar fell sharply last year. What part was played by the adverse “fundamentals” of the US economy, the large current account deficit, the country's heavy foreign indebtedness and the substantial budget deficit? How will the dollar behave in future?
Keywords: 330; Monetary Policy